The nursification of a bioscience unit and its impact on student satisfaction and learning in an undergraduate nursing degree. (May 2018) - Mortimer-Jones, Sheila; Fetherston, Catherine
Abstract: Undergraduate nursing students traditionally find bioscience difficult, which can be compounded by an inability to relate bioscience theory to nursing practice. Subsequently, many registered nurses feel they lack knowledge in this area. Several studies have identified this problem and focused on the importance of linking bioscience theory in undergraduate nursing curricula to clinical practice. The aim of this study was to assess whether nursification (the active association of a subject with nursing theory and practice) of the bioscience content of a first year, first semester unit impacts on the students' learning experience. The study compared two student groups' perceptions of their learning experience; one group enrolled before the bioscience unit was linked to nursing practice (pre-nursification) and the other group enrolled after the content was linked to nursing practice (post-nursification). Retrospective, quantitative analysis of the mean scores of the student feedback surveys found no significant difference between the pre and post-nursification responses with respect to the students' overall satisfaction of the unit or their ability to achieve their learning objectives, however the students in the post-nursification group reported significantly higher mean scores with respect to their motivation and inspiration to learn, and to learn effectively. The findings in this study suggest that integration of nursing practice within a bioscience unit can improve the learning experience of undergraduate nursing students. Highlights: Nursification is defined as the active association of a subject with nursing theory and practice. Retrospective quantitative analysis of nursing student feedback surveys in an undergraduate course to observe how nursification impacts on their learning experience. Feedback scores of students' motivation and inspiration to learn, and to learn effectively, increased after nursification of the bioscience unit content.